Lipid droplets contribute myogenic differentiation in C2C12 by promoting the remodeling of the acstin-filament - Yanjie Tan (Nature Publishing Group, 2021)
Abstract Lipid droplet (LD), a multi-functional organelle, is found in most eukaryotic cells. LDs participate in the regulation of many cellular processes including proliferation, stress, and apoptosis. Previous studies showed the athlete’s paradox that trained athletes accumulate LDs in their skeletal muscle. However, the impact of LDs on skeletal muscle and myogenesis is not clear. We discovered that C2C12 myoblast cells containing more LDs formed more multinucleated muscle fibers. We also discovered that LDs promoted cell migration and fusion by promoting actin-filaments remodeling. Mechanistically, two LD-proteins, Acyl-CoA synthetase long chain family member 3 (ACSL3) and lysophosphatidylcholine acyltransferase 1 (LPCAT1), medicated the recruitment of actinin proteins which contributed to actin-filaments formation on the surface of LDs. During remodeling, the actinin proteins on LDs surface translocated to actin-filaments via ARF1/COPI vesicles. Our study demonstrate LDs contribute to cell differentiation, which lead to new insight into the LD function.